2013
DOI: 10.2298/abs1302559d
|View full text |Cite
|
Sign up to set email alerts
|

Studies of ecomorphological variations of the European hare (Lepus europaeus) in Turkey

Abstract: Hares (Lepus spp.) are widely distributed across the globe and are adapted to diverse climatic conditions. In order to study the ecomorphological variations of hares from Turkey, the body and cranial measurements and body weight, as well as coat color types, of 138 hares collected from all over Turkey between 2006 and 2012, were examined. Statistically significant differences between regional samples (p <0.05, ANOVA) only in terms of body weight and hindfoot length were found; however, there were a good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…On the basis of the estimated densities, available mean prey biomass was calculated by using an average adult live body weight of 3.17 kg for brown hare (Demirbaş, Albayrak, & Yilmaz, ) and three‐fourth of female adult live body weights of 75 kg for red deer, 30 kg for wild goat, and 60 kg for wild boar to account for juveniles (Turan, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the estimated densities, available mean prey biomass was calculated by using an average adult live body weight of 3.17 kg for brown hare (Demirbaş, Albayrak, & Yilmaz, ) and three‐fourth of female adult live body weights of 75 kg for red deer, 30 kg for wild goat, and 60 kg for wild boar to account for juveniles (Turan, ).…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the estimated densities, available mean prey biomass was calculated by using an average adult live body weight of 3.17 kg for brown hare (Demirbaş, Albayrak, & Yilmaz, 2013) and three-fourth of female adult live body weights of 75 kg for red deer, 30 kg for wild goat, and 60 kg for wild boar to account for juveniles (Turan, 1984 Chesson's selectivity index α (Chesson, 1978) was then used to assess lynx prey preferences. Chesson's α is defined as the proportion of prey species in the scat divided by the proportion of prey species i in the environment, p i , normalized in such a way that the sum of the alpha values over all k prey species equals one (Chesson, 1978).…”
Section: Prey Preferencesmentioning
confidence: 99%
“…Demirbaş et al (2012) noted that despite the presence of different phenotypes in Anatolia, genetic exchange is rather low among these hares. Additionally, Demirbaş et al (2013) found significant differences in some morphometric characters among regional hare samples in Turkey. It was concluded that climatic characteristics, particularly with ambient temperature, cause plasticity in the reproductive cycle of European hare populations distributed in Turkey.…”
mentioning
confidence: 89%